Developing Pre-service Secondary Teachers' Skills of Using the Geometer's Sketchpad to Teach Mathematics through Lesson Study - Meng, Chew Cheng; Sam, Lim Chap; Yew, Wun Thiam; Lian, Lim Hooi (Sains Humanika, 2013)
The purpose of this study was to develop pre-service secondary teachers’ skills of using The Geometer’s Sketchpad (GSP) to teach mathematics through Lesson Study (LS). GSP is a dynamic geometry software program for constructing and investigating mathematical objects that adds a powerful dimension to the teaching and learning of geometry and many other areas of mathematics. Lesson Study is a Japanese model of teacher professional development in which small groups of teachers collaboratively plan, teach and revise a lesson to improve the quality of their teaching as well as to enrich students’ learning experiences. Twenty-three LS groups comprising 2 pre-service secondary teachers who attended a mathematics teaching methods course in a local public university were set up in four tutorial groups each consisting of five or six LS groups. This paper discusses how LS has helped to develop pre-service secondary teachers’ skills of using GSP to teach the topic of ‘Loci in Two Dimensions’ in one of the LS groups. Analysis of their GSP sketches in the first, second and third lessons indicates that the participants of this LS group showed positive changes in their skills of using GSP to teach the topic.